Pengaruh Daya Tarik Influencer dan Brand Image Terhadap Keputusan Pembelian Produk Skincare (Studi Pada Konsumen Glad2Glow di Kalangan Gen Z) - Pratiwi, Defanny Rahman; Hermawati, Ati (Jurnal EMT KITA, 2026)
This study aims to determine the development of social media that has changed marketing strategies by promoting highly attractive influencers to influence consumer behavior, particularly in the increasingly competitive beauty industry as Gen Z's interest in skincare products grows. The sampling method used was Non-Probability Sampling with Purposive Sampling technique with a sample size of 100 respondents. Data collection was conducted using a questionnaire distributed via Google Form using a Likert scale. The results were analyzed using multiple linear regression analysis, classical assumption tests, hypothesis testing, and data processing using SPSS 30. The results showed that influencer appeal and brand image had a positive and significant effect on purchasing decisions, both partially and simultaneously. These findings confirm that the synergy between attractive influencers and strong brand image can increase consumer purchasing decisions. The practical implications underscore the importance of selecting influencers that are in line with the brand identity and consistently building a positive image on social media.